Stable analogs of 13‑hydroxy-9, 10-trans-epoxy-(11E)-octadecenoate (13, 9-HEL), an oxidized derivative of linoleic acid implicated in the epidermal skin barrier. (November 2021) - Keyes, Gregory S.; Maiden, Kristen; Ramsden, Christopher E.
Highlights: Oxidized derivatives of linoleic acid proposed to play essential role in formation of epidermal skin barrier. Total organic synthesis provides racemic mixtures of oxidized derivatives of linoleic acid useful for probing the essential nature of this fatty acid. Organic synthesis also provides stable analogs and buffer soluble small molecule probes containing key functional groups of oxidized linoleic acid derivatives, resistant to further oxidation or to esterification. Total synthesis of oxidized derivatives of sebaleic acid, a regioisomer of linoleic acid present in skin. Abstract: Hydroxy-epoxy- and trihydroxy derivatives of linoleic acid are proposed to play an essential function in formation of the mammalian skin permeability barrier, which could account for the essential nature of its precursor, linoleic acid. Recent literature suggests that a specific oxidized enone derivative of LA esterified in ceramides facilitates binding to proteins, potentially serving a structural role in formation of the epidermal skin barrier. However, it is still to be established if other linoleic acid derivatives are also required for skin barrier formation, and whether the essential role is performed exclusively by an esterified, structural lipid or as an unesterified, labile signaling lipid, or by some combination of these derivatives. Progress in this domain is limited by lack of availability of hydroxy‑epoxy-and trihydroxy- and octadecenoate derivatives of linoleic acid and related compounds, and challenges in maintaining them in the unesterified lipid pool. Here we describe methods for the total synthesis of hydroxy‑epoxy-octadecenoate derivatives of linoleic acid (HEL 1 ), and stable analogs that are designed to be resistant to inactivation by: (a) acylation/esterification (thus trapping these lipids in the free acid pool), (b) dehydrogenation, and (c) analogs combining both modifications. We further provide a total synthesis of corresponding hydroxy‑epoxy- derivatives of sebaleic acid (a regioisomer of linoleic acid present in skin), and of small molecule scaffolds containing the allylic and non-allylic epoxide 7-carbon substructures shared by both families of hydroxy‑epoxy-and trihydroxy- octadecenoates. Finally, we demonstrate that 2, 2-dimethyl analogs of hydroxy‑epoxy-and trihydroxy- octadecenoates are resistant to esterification with an in vitro assay and thus provide a novel template for stabilizing labile, bioactive lipids as free acids by preventing acylation/esterification.